Flap Viability after Direct Immediate Application of Negative Pressure Wound Therapy on Free Flaps: A Systematic Review and Pooled Analysis of Reported Outcomes - Opoku-Agyeman, Jude L.; Matera, David V.; Simone, Jamee E.; Behnam, Amir B. (Journal of Reconstructive Microsurgery Open, 2019)
Background The use of negative pressure wound therapy (NPWT) devices has gained wide acceptance in the management of wounds. There have been a few reported cases of its use immediately after free tissue transfer. This is the first systematic review and pooled analysis on the immediate use of NPWT for free flaps with emphasis on the rate of free flap loss.Methods The authors performed a systematic review that focused on the rate of total free flap loss after immediate application of NPWT. EMBASE, Cochrane Library, Ovid Medicine, MEDLINE, Google Scholar, and PubMed databases were searched from 1997 to April of 2019. Peer-reviewed articles published in the English language were included.Results Ten articles were included in the review, yielding 211 free flap procedures. All studies were retrospective cohort studies except for two that were prospective studies and one that was a case series. The overall complete flap failure rate was n = 7 (3.3%). The most commonly reconstructed area was the lower extremity (n = 158 [74.9%]) followed by head and neck (n = 42 [19.9%]) and upper extremity (n = 11 [5.2%]). The vacuum pressure ranged from 75 to 125 mm/Hg. The time of application of the NPWT ranged from 5 to 7 days. The etiologies of wound defects were from trauma (n = 82 [63.6%]), tumor extirpation (n = 43 [33.3%]), and infection and burn (n = 4 [3.1%]).Conclusion The immediate application of NPWT on free flaps does not seem to be associated with an increased risk of flap failure.
Keywords: NPWT; free flap; microvascular free flap